Analisis Trafik Jaringan menggunakan Wireshark untuk Deteksi Serangan Deauthentication pada Perangkat Kamera Wi-Fi - Putri, Anisa Febriyana; Hadi, Abdul; Rusdiana, Lili (Jurnal Saintekom : Sains, Teknologi, Komputer dan Manajemen, 2025)
The widespread adoption of wireless networks has increased the popularity of Wi-Fi-based cameras due to their ease of installation and flexibility. However, Wi-Fi devices are highly vulnerable to deauthentication attacks, a type of denial-of-service (DoS) attack that repeatedly disconnects devices from the network without user awareness. This study presents a controlled experiment simulating deauthentication attacks on Wi-Fi cameras and detecting them using Wireshark. The findings demonstrate that these attacks consistently disrupt camera connectivity, causing interruptions of 50 seconds to 1 minute and 18 seconds across two scenarios. In the first scenario, the camera connection temporarily recovered between disruptions, while in the second, it remained in a reconnecting state without restoration. All attacks were successfully identified through captured deauthentication packets. This work provides experimental validation of a widely used deauthentication attack technique leveraging the Kali Linux operating system, emphasizing its significant impact on Wi-Fi cameras. Furthermore, it highlights the importance of developing mitigation strategies to address this threat in real-world environments.